artikel Analisis Kampanye UMJ Green Campus by Treecycle Project - Abdurrahman Zaviier; Marsan Almuzaki; Sa'diyah El Adawiyah (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
This study will analyze the "UMJ GREEN CAMPUS" campaign organized by the treecycle project of 5th semester communication science students at Muhammadiyah University of Jakarta, the current environmental conditions at Muhammadiyah University of Jakarta are quite worrying, from scattered garbage to the lack of trees in the campus environment, these things have an extraordinary impact if no action is taken immediately, the fundamental problem of this problem is that the awareness of Muhammadiyah University of Jakarta students regarding environmental concerns is very, very low, as easy as processing waste, there is a lack of social concern by Muhammadiyah University of Jakarta students, after realizing the issues regarding the environment that occur at Muhammadiyah University of Jakarta, the treecycle project which is driven by 5th semester communication science students at Muhammadiyah University of Jakarta under the guidance of lecturer Mrs. Syifa Atasia Utari S.I.Kom, M.Si they created a "UMJ GREEN CAMPUS" campaign program in the hope of providing good changes to the environment of Muhammadiyah University of Jakarta, with a variety of series of programs that are organized they design and planning a better environment for Muhammadiyah University of Jakarta.